Evaluation of basketball-specific agility: Applicability of preplanned and nonplanned agility performances for differentiating playing positions and playing levels - Sekulic, D.; Pehar, M.; Krolo, A.; Spasic, M.; Uljevic, O.; Calleja-Gonzalez, J.; Sattler, T. (The Journal of Strength and Conditioning Research, 2017)
The importance of agility in basketball is well known, but there is an evident lack of studies examining basketball-specific agility performances in high-level players. The aim of this study was to determine the reliability and discriminative validity of 1 standard agility test (test of preplanned agility [change-of-direction speed] over T course, T-TEST), and 4 newly developed basketball-specific agility tests, in defining playing positions and performance levels in basketball. The study comprised 110 high-level male basketball players (height: 194.92 ± 8.09 cm; body mass: 89.33 ± 10.91 kg; age: 21.58 ± 3.92 years). The variables included playing position (Guard, Forward, Center), performance level (first division vs. second division), anthropometrics (body height, body mass, and percentage of body fat), T-TEST, nonplanned basketball agility test performed on dominant (BBAGILdom) and nondominant sides (BBAGILnond), and a preplanned (change-of-direction speed) basketball agility test performed on dominant (BBCODSdom) and nondominant sides (BBCODSnond). The reliability of agility tests was high (intraclass correlation coefficient of 0.81-0.95). Forwards were most successful in the T-TEST (F test: 13.57; p = 0.01). Guards outperformed Centers in BBCODSdom, BBCODSndom, BBAGILdom, and BBAGILnond (F test: 5.06, p = 0.01; 6.57, 0.01; 6.26, 0.01; 3.37, 0.04, respectively). First division Guards achieved better results than second division Guards in BBCODSdom (t: 2.55; p = 0.02; moderate effect size differences), BBAGILdom, and BBAGILnond (t: 3.04 and 3.06, respectively; both p = 0.01 and moderate effect size differences). First division Centers outperformed second division Centers in BBAGILdom (t: 2.50; p = 0.02; moderate effect size differences). The developed basketball-specific agility tests are applicable when defining position-specific agility. Both preplanned and nonplanned agilities are important qualities in differentiating between Guards of 2 performance levels. The results confirmed the importance of testing basketball-specific nonplanned agility when evaluating the performance level of Centers.